Character Characters in the Novel Putri Komodo by Michael Yudha Winarno - Reva Deviana; Rian Hidayat (UIR Press, 2022)
Imaginative literary works are the result of the wishful thinking of an author. The author describes a picture of a person's life through novels. This research is entitled